Allahabad High Court to Shah Commission - "Bright, J. S." (New Delhi, 1979)
"Allahabad High Court to Shah Commission" is the most dramatic episode in the democratic history of India; and its effects shall never be wiped out but have a chain reaction extending to hundreds of years, because in the laboratory of universal phenomena every cause generates an effect and the effect itself becomes a cause for yet another effect, leading to infinity, like whirls of waves in a placid pool of water in which a stone has been thrown. And Emergency was nothing but a stone hurled carelessly (or carefully ?), thoughtlessly (or thoughtfully ?) in the cosmic calmness of the Indian Ocean.
Keywords: IndiaPolitics & Govt